2021
DOI: 10.3390/nu13093117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Polymorphism and Vitamin D Status in Population of Patients with Cardiovascular Disease—A Preliminary Study

Abstract: The association between vitamin D receptor (VDR) polymorphism and the risk of cardiovascular diseases (CVD) remains unclear. This study aimed to assess a relationship between the VDR genotypes, plasma concentrations of vitamin D metabolites, and the occurrence of cardiovascular and metabolic disorders. Fifty-eight patients treated for various cardiological afflictions were included. Identification of VDR polymorphisms: ApaI, TaqI, BsmI, and FokI were carried out using the PCR-RFLP method. Plasma concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
4
10
0
Order By: Relevance
“…In our study, the logistic regression analysis adjusted for body mass index and diabetes revealed that the VDR FokI TT genotype showed an association with increased risk of CVD in the genotypic model ( p < 0.05; Table 3 ) and in the recessive model ( p < 0.05; Table 3 ). Several studies are consistent with our results, for example one study conducted in a Caucasian population (from Poland) (58 cases/142 controls), in which statistically significant differences were found in relation to the T allele of the VDR FokI polymorphism, identifying it as a risk factor for heart failure and hypertension ( p = 0.03) [ 55 ]. Another study in a Caucasian population (from Egypt) (50 cases/50 controls) also reported an association between the VDR FokI polymorphism and the presence of congenital heart disease defects.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the logistic regression analysis adjusted for body mass index and diabetes revealed that the VDR FokI TT genotype showed an association with increased risk of CVD in the genotypic model ( p < 0.05; Table 3 ) and in the recessive model ( p < 0.05; Table 3 ). Several studies are consistent with our results, for example one study conducted in a Caucasian population (from Poland) (58 cases/142 controls), in which statistically significant differences were found in relation to the T allele of the VDR FokI polymorphism, identifying it as a risk factor for heart failure and hypertension ( p = 0.03) [ 55 ]. Another study in a Caucasian population (from Egypt) (50 cases/50 controls) also reported an association between the VDR FokI polymorphism and the presence of congenital heart disease defects.…”
Section: Discussionsupporting
confidence: 90%
“…Another study conducted by Caccamo et al [ 40 ] suggested an association between gestational hypertension and the VDR FF haplotype. In accordance with previous study Abouzid et al [ 38 ] reported that Fok I SNP TT genotype was associated with a higher incidence of heart failure and hypertension.…”
Section: Fok I Polymorphism and Essential Hypertensionsupporting
confidence: 92%
“…Both SNPs were not associated with DM. Abouzid et al [ 38 ] 2021 Poland Preliminary Bsm I, Apa I, Fok I, Taq I CVD Apa I, Tag I, and Bsm I was found to be associated with an increased risk of obesity. Fok I was associated with a higher incidence of heart failure and hypertension.…”
Section: Vitamin D Receptor Polymorphismsmentioning
confidence: 99%
“…In conclusion, this study reported that the BsmI AA genotype can be protective against CVS, but this observation needs to be con rmed on a larger group of patients. Particular VDR genotypes were associated with 25-hydroxyvitamin-D levels, and the mechanism of this association should be further investigated 22 . Another cross-sectional study investigated relationships of vitamin D receptor gene VDR polymorphisms to the components of metabolic syndrome (MetS) including obesity, hypertension, diabetes and dyslipidemia among 198 (148 females, 50 males) Arabs adult residing in the United Arab Emirates reported that VDR gene polymorphisms were not associated with MetS.…”
Section: Genotypes and Allele Percentage Frequency Distribution In Su...mentioning
confidence: 99%
“…For Taql VDR genotype our result agree with another study ndings from the UAE and a study from France 12,21 . Although not many studies in the UAE have reported the frequency distribution of the SNP3 Apal however studies from the Middle East have reported the relationship between SNP3 Apal and vitamin D and occurrence of cardiovascular disease (CVS) from around the world 22 . Our results of SNP4 Fok1 genotypes & allele percentage frequency distribution are different from previous studies including one from the UAE 12 .…”
Section: Genotypes and Allele Percentage Frequency Distribution Compa...mentioning
confidence: 99%